1939
DOI: 10.1111/j.1651-2227.1939.tb16919.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Roentgen‐anatomical Appearance of Congenital Pyloric Stenosis during and after the Manifest Stage of the Disease

Abstract: Summary. Pyloric stenosis in infants has a typical roentgen‐anatomical appearence. In the manifest stage the canalis egestorius is contracted to a narrow, streak‐like lumen, 2—3 cm in length. The stomach shows stenosal peristalsis, which does not pass beyond the oral limit of the constriction. The duodenal cap is normal in shape and size. The opening time of the stomach is prolonged up to 2 hours (Stage I). After the cessation of the manifest symptoms up to 4 years the opening time is normal and the lumen of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1941
1941
1990
1990

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Similar findings have been demonstrated by Runstrom (1939), in a radiographic follow-up of medically treated patients. Runstrom is, however, of the opinion that the abnormalities disappear in all patients about the age of puberty.…”
Section: Discussionsupporting
confidence: 85%
“…Similar findings have been demonstrated by Runstrom (1939), in a radiographic follow-up of medically treated patients. Runstrom is, however, of the opinion that the abnormalities disappear in all patients about the age of puberty.…”
Section: Discussionsupporting
confidence: 85%
“…as suggested by McConnell (1966), the adult disease is not severe enough to give obstructing symptoms in infancy. Runstrom (1939) and…”
Section: Case Reportsmentioning
confidence: 99%
“…Runstrom (1939) studied 107 children with congenital pyloric stenosis treated medically and showed that the radiological abnormalities became less frequent with advancing years, but were still present long after there were no symptoms. Lumsden and Truelove (1958), in 17 patients between the ages of 14 and 25 years, confirmed this and showed that the fading-out process continued into full adult life.…”
Section: Aetiologymentioning
confidence: 99%
“…It is hard to explain the long gap between birth and the onset of symptoms in some patients or why the hypertrophy might worsen later in life. A complicating factor, such as mucosal oedema (Runstrom, 1939), may precipitate the symptoms of pyloric occlusion. It is probably relevant to note, therefore, that complicated adult hypertrophy is more common than the simple variety, and that usually the duration of symptoms is shorter.…”
Section: Aetiologymentioning
confidence: 99%